Decoupling analysis of brushless dual-mechanical-port dual-electrical-port machines - Cao, Libing (2023)
The brushless dual-mechanical-port dual-electrical-port (BLDD) machine has emerged as a promising alternative to the traditional mechanical continuously variable transmission (CVT), due to its gearless and brushless design. In BLDD machines, two sets of windings are placed in the same stator, and care must be taken to avoid strong coupling that may deteriorate the machine performance and reliability. This paper categorizes the topologies of existing BLDD machines into five types and presents a systematic decoupling analysis from the perspective of field-modulation theory. Using the presented method, the conditions to achieve decoupled designs are concluded and the decoupling characteristics of each type of BLDD machine are identified. Besides, a simple indicator is developed to fast identify the coupling type, i.e., decoupled, low or high coupling design, of BLDD machines, enabling an efficient selection of slot-pole combinations. With the aid of finite-element analysis (FEA), the coupling degree of BLDD machines with various slot-pole combinations has been analyzed for verification. Other performances, such as torque density and PM utilization, are also compared among the five types of BLDD machines to provide a more comprehensive view of their characteristics. Finally, a prototype of a BLDD machine is manufactured and tested to validate the analysis.